2022
DOI: 10.1007/s11356-021-18302-8
|View full text |Cite
|
Sign up to set email alerts
|

High concentrations of pharmaceuticals emerging as a threat to Himalayan water sustainability

Abstract: The sixth UN Sustainable Development Goal, Clean Water and Sanitation, directly underpins other goals of Health, Life in Water and Sustainable Cities. We highlight that poor sanitation, exemplified through some of the highest concentrations of pharmaceuticals ever detected in rivers, will amplify societal and environmental stress where climate-induced reductions in flow are predicted. Rapidly growing urban centres with inadequate water treatment works will need to prioritise water quality improvement before su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…This is common in heavily exploited Mediterranean rivers (IMPREX 2020 ). Seasonal reductions in water river flow may also increase the contaminant concentration of pharmaceuticals and hence their potential toxicity and risks since their consumption varied little across the year (Quincey et al 2022 ). Our study was performed in late autumn and winter, which are characterized by being moderately dry, and thus, the Llobregat river water flow is moderate.…”
Section: Resultsmentioning
confidence: 99%
“…This is common in heavily exploited Mediterranean rivers (IMPREX 2020 ). Seasonal reductions in water river flow may also increase the contaminant concentration of pharmaceuticals and hence their potential toxicity and risks since their consumption varied little across the year (Quincey et al 2022 ). Our study was performed in late autumn and winter, which are characterized by being moderately dry, and thus, the Llobregat river water flow is moderate.…”
Section: Resultsmentioning
confidence: 99%
“…This is common in heavily exploited Mediterranean rivers ("imprex.eu"). Seasonal reductions in water river flow may also increase the contaminant concentration of pharmaceuticals and hence their potential toxicity and risks since their consumption varied little across the year (Quincey et al 2022). Our study was performed in late autumn and winter, which are characterized by being moderately dry and thus the Llobregat river water flow is moderate.…”
Section: Risk Assessmentmentioning
confidence: 99%
“…The study of Cappelli et al [23] found eight pharmaceutical compounds of high ecological concern from a WWTP of Italy which received the sewages from a hospital dedicated for the treatment of COVID-19 patients. Quincey et al [24] showed the presence of 28of -35 monitored human-use pharmaceuticals in 23 river sites which are at risk of proliferating antimicrobial resistance (AMR) and other toxicological endpoints within Kathmandu City and the Annapurna region of Nepal. The global scale study performed by Wilkinson et al [4] shown carbamazepine, metformin, and caffeine as active pharmaceutical contaminants in surface waters of 1052 sampling sites along 258 rivers in 104 countries.…”
Section: Toxic Effects On Aquatic Ecosystemmentioning
confidence: 99%
“…Aeromonas caviae and A. hydrophila in Indian carps obtained from the local market in Kolkata, India. Quincey et al (2022) [24] reported 28 high risks from human drugs at 23 river sites in the city of Kathmandu and the Annapurna region of Nepal.…”
Section: Amr Evolutionmentioning
confidence: 99%